2001
DOI: 10.1128/jvi.75.14.6329-6336.2001
|View full text |Cite
|
Sign up to set email alerts
|

A Nonviral Peptide Can Replace the Entire N Terminus of Zucchini Yellow Mosaic Potyvirus Coat Protein and Permits Viral Systemic Infection

Abstract: Systematic deletion and peptide tagging of the amino-terminal domain (NT, ϳ43 amino acids) of an attenuated zucchini yellow mosaic potyvirus (ZYMV-AGII) coat protein (CP) were used to elucidate its role in viral systemic infection. Deletion mutants truncated by 8, 13, and 33 amino acid residues from the CP-NT 5 end were systemically infectious and produced symptoms similar to those of the AGII virus. Tagging these deletion mutants with either human c-Myc (Myc) or hexahistidine peptides maintained viral infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 36 publications
2
30
0
1
Order By: Relevance
“…Therefore, we modified the expression levels of TIPK by employing an attenuated potyvirus vector, ZYMV-AGII (Arazi et al, 2001). This vector represents a unique system for gene expression in cucurbit cytosol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we modified the expression levels of TIPK by employing an attenuated potyvirus vector, ZYMV-AGII (Arazi et al, 2001). This vector represents a unique system for gene expression in cucurbit cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…Because it was engineered from an attenuated strain, it is nonpathogenic and does not impair growth of the host plant (Arazi et al, 2001). The AGII-GFP construct has been reported to be stable in cucumber plants for at least 60 dpi (Arazi et al, 2001), and we also validated the propagation of the virus during our experimental period. We determined the stability of the viral constructs throughout the experiments (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, neither the insertion site used nor specific affinity tag-based purification of potyviral VPg has been described previously. Epitope-tag insertions coupled with purification have been reported for the potyviral proteins HC-Pro, 6K2 and CP (Restrepo-Hartwig & Carrington, 1994;Blanc et al, 1999;Arazi et al, 2001). Successful purification under native conditions showed that the affinity tag, and hence the C terminus of VPg, was exposed on the surface of both VPg and NIa.…”
Section: Discussionmentioning
confidence: 99%
“…Además de dichos estudios básicos, estos virus también se han utilizado para expresar en plantas genes foráneos de diferentes tipos. Por ejemplo, con el virus del mosaico amarillo del calabacín (Zucchini yellow mosaic virus, ZYMV) se ensayó la expresión de un epítopo inmunogénico del virus de la fiebre aftosa insertado en el área amino terminal de la proteína de la cápside (evaluando variadas deleciones dentro de la misma), y se ha comprobado que dicha región no es necesaria para el movimiento sistémico viral (Arazi et al, 2001a). Asimismo, con una cepa atenuada de este virus se ha probado la expresión del gen del interferón alfa-2 humano en plantas de calabaza y pepino (Arazi et al, 2001b), y también la adquisición de resistencia a herbicidas que contienen glufosinato de amonio en plantas de melón, pepino, calabaza y sandía gracias a la expresión del gen bar, que codifica para la fosfinotricina acetiltransferasa (Shibolet et al, 2001).…”
Section: Los Virus Como Vectores De Expresión De Proteínasunclassified